2019
DOI: 10.3389/fimmu.2019.01533
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking the Supplies: Metabolism as a Novel Facet of Virus-Host Interaction

Abstract: Viral replication is a process that involves an extremely high turnover of cellular molecules. Since viruses depend on the host cell to obtain the macromolecules needed for their proper replication, they have evolved numerous strategies to shape cellular metabolism and the biosynthesis machinery of the host according to their specific needs. Technologies for the rigorous analysis of metabolic alterations in cells have recently become widely available and have greatly expanded our knowledge of these crucial hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
161
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(165 citation statements)
references
References 113 publications
(163 reference statements)
4
161
0
Order By: Relevance
“…Viruses are a major contributor to the global burden of diseases because they cause acute and chronic infectious diseases [26,27]. Many studies have shown how viruses hijack cellular pathways and evade the host's innate immune response, starting from entry, until the virus exits from host cells by modulating host factors and signaling pathways [28,29]. Therefore, comprehensive knowledge of host-virus interactions is important in order to understand the viral life cycle and to develop specific therapeutic approaches for the treatment of viral infections.…”
Section: Host-virus Interactionsmentioning
confidence: 99%
“…Viruses are a major contributor to the global burden of diseases because they cause acute and chronic infectious diseases [26,27]. Many studies have shown how viruses hijack cellular pathways and evade the host's innate immune response, starting from entry, until the virus exits from host cells by modulating host factors and signaling pathways [28,29]. Therefore, comprehensive knowledge of host-virus interactions is important in order to understand the viral life cycle and to develop specific therapeutic approaches for the treatment of viral infections.…”
Section: Host-virus Interactionsmentioning
confidence: 99%
“…Thus, it is not surprising that viruses and infected cells have co-evolved to develop measures and countermeasures to promote or restrict virus replication, respectively. This battle results in a profound impact of virus infection on the host cell's metabolism [1][2][3]. Also, this dependence of viruses on cell metabolism provides new intervention opportunities for limiting virus replication.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Many extensive reviews detail viral reprogramming of host cell metabolism, and for brevity, we refer readers elsewhere. [8][9][10][11] A variety of viruses stimulate increased glycolysis to drive the production of energy-rich molecules, such as ATP, NADH, and NADPH. Glycolysis can also supply a carbon pool for the synthesis of nucleotides, lipids, and amino acids for macromolecule production.…”
mentioning
confidence: 99%